Perbandingan efektivitas metode partisipatif dengan nformatif dalam meningkatkan pengetahuan dan sikap ibu tentang diare anak balita - Syafie Ishak, Djauhar Ismail, Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Diarrhea is one of the infectious diseases and is the main cause of under-fiveyear-old children's morbidity and mortality in Indonesia especially children aged less than two years. Many diseases or health conditions of the people result from or get worse from their behavior. One of the ways to change the attitude people's behavior in health is the increase of knowledge and people's behavior with health educational approach using various methods. Objectives: This study was aimed at finding out the difference between increasing knowledge and attitude of mothers about diarrhea of under-five-year-old children and their treatment at home by using participatory method of education and informative method. Methods: This was a quasi experimental study using nonrandomized pretest-posttest control group design. The subjects were mothers with under-five-year-old children. There were 68 samples, 34 of whom were in the treatment group and the other 34 were in the control group and each was in Tegalrejo village and Dukuh Dungus village, Grabag Sub-District, Purworejo Regency. Data analysis using chi-square was used to test the group's homogeneity, t-test was to test the difference of average rate of knowledge and attitude, and multiple regression analysis was used to know the effect of other variables or the dependent variables. Results: The results showed statistical significant difference (p0.05). In terms of mothers' increasing knowledge and attitude toward diarrhea from pretest 1 to posttest, both methods statistically showed significant increase (p0.05). Conclusion: Health education through participatory method is more effective than increasing knowledge and this was less effective to increase mothers' attitude on diarrhea compared with informative method. Keywords: educational method, knowledge, attitude, under-five-year-old children, diarrhea